Some Evidence on Potential Effects of Contemporaneous Earnings Disclosures in Tests of Capital Market Effects Associated with FASB Exposure Draft No. 19 - Waymire, Gregory; Pownall, Grace (Journal of Accounting Research, 1983)
Gregory Waymire, Grace Pownall, Some Evidence on Potential Effects of Contemporaneous Earnings Disclosures in Tests of Capital Market Effects Associated with FASB Exposure Draft No. 19, Journal of Accounting Research, Vol. 21, No. 2 (Autumn, 1983), pp. 629-643